Modeling a tourism regional cluster: the impact of administrative and logistic restrictions on the development of regulated clusters - Dukhovnaya, Liliya; Sayenko, Maria; Zenin, Sergey; Kryukova, Elena; Sekerin, Vladimir; Sinyukov, Vasily (Anais Brasileiros de Estudos Turísticos, 2023)
The article proposes a tourism cluster structure dividing it into four main sectors: the production of tourism services (tourism enterprises, accommodation, catering, and transport services), the service sector, the auxiliary sector, and the life support sector. The article systematizes various models of regional tourism clusters depending on the distribution of roles, areas of interaction, the impact of integration, and the stages of the cluster life cycle: a non-core cluster, an axial cluster, a satellite cluster, and a regulated cluster. Authors concluded that due to the crisis caused by the pandemic, sanctions, and trade wars, the role of regulated tourist clusters in Russia will only increase since these clusters are more stable due to state support. In relation to external restrictions on outbound tourism, the state will focus on the development of domestic tourism while regulating the activities of tourism clusters. In this case, new projects of large-sized tourism businesses will be aimed not to obtain economic benefits but rather to demonstrate their loyalty to the existing government. On the contrary, businesses will rely on subsidies and economic support from the state.